Extracellular vesicle fusion visualized by cryo-electron microscopy. Issue 4 (16th August 2022) - Morandi, Mattia I; Busko, Petro; Ozer-Partuk, Efrat; Khan, Suman; Zarfati, Giulia; Elbaz-Alon, Yael; Abou Karam, Paula; Napso Shogan, Tina; Ginini, Lana; Gil, Ziv; Regev-Rudzki, Neta; Avinoam, Ori
Abstract: Extracellular vesicles (EVs) transfer bioactive molecules between cells in a process reminiscent of enveloped viruses. EV cargo delivery is thought to occur by protein-mediated and pH-dependent membrane fusion of the EV and the cellular membrane. However, there is a lack of methods to identify the fusion proteins and resolve their mechanism. We developed and benchmarked an in vitro biophysical assay to investigate EV membrane fusion. The assay was standardized by directly comparing EV and viral fusion with liposomes. We show that EVs and retroviruses fuse with liposomes mimicking the membrane composition of the late endosome in a pH- and protein-dependent manner. Moreover, we directly visualize the stages of membrane fusion using cryo-electron tomography. We find that, unlike most retroviruses, EVs remain fusogenic after acidification and reneutralization. These results provide novel insights into the EV cargo delivery mechanism and an experimental approach to identify the EV fusion machinery.